(3EJeGe GdOQGjI dbQGA GdfbGjIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3eMehO Hf QGDs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi fYeg GdTGedI hHYO adeG XgQ dj JUhjH GdedMjf Ydqj aj hVY TQM Ydi GdcQGSI GdJj SejJgG HGdfbGjI HGOQJ Edi Pdc hSejJg HEJeGe GdOQGjI dbQGA GdfbGjI s
(3BNQgG (B:s
(3hJaGhJ GdeQGJH aj GdOfjG hGdBNQI dG QGO dbVGFg HGdOaY hdG eYbH dMceg HGdfbV SHMGfg hJYGdi gPG BNQ EJeGe GdOQGjI dbQGA GdfbGjIs
(3aj Chdg fbhd aj Gdabg hGdMOjK (B- (3Hg YdGeGJ eGFjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3/301s
(3eYLe GdeDdajf (B2/82s
(3cTa GdXfhf (B2 / 1970s
(3TPQGJ GdPgH (B8/51s
Keywords: (3GdeYGQa GdYGeIs